1928
DOI: 10.1084/jem.47.3.379
|View full text |Cite
|
Sign up to set email alerts
|

On the Rôle of Carbohydrate Haptens in Bacterial Anaphylaxis

Abstract: Though the existence of bacterial anaphylaxis was demonstrated by Rosenau and Anderson (1) as early as 1907, subsequent investigators could not diminish the difficulties in producing a clear-cut anaphylactic shock with the majority of microorganisms. The main difficulty in the study of bacterial anaphylaxis is the primary toxicity of the bacterial protein. According to Doerr (2) the amount of bacterial antigen which produces shock in sensitized animals is negligibly smaller than the lethal dose for normal anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1929
1929
1944
1944

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In addition, he found that the isolated uterus of a sensitized guinea pig reacted to exceedingly small quantities of the material. These observations were extended by Tomcsik and Kurotchkin (2) to include the carbohydrates obtained from the pneumobacillus and from yeast. In 1929 Avery and Tillett (3) confirmed the work of these authors by producing with the specific carbohydrate of the pnenmococcus anaphylactic shock in guinea pigs treated with antipneumococcus rabbit sera corresponding to Types I, II and III.…”
mentioning
confidence: 80%
“…In addition, he found that the isolated uterus of a sensitized guinea pig reacted to exceedingly small quantities of the material. These observations were extended by Tomcsik and Kurotchkin (2) to include the carbohydrates obtained from the pneumobacillus and from yeast. In 1929 Avery and Tillett (3) confirmed the work of these authors by producing with the specific carbohydrate of the pnenmococcus anaphylactic shock in guinea pigs treated with antipneumococcus rabbit sera corresponding to Types I, II and III.…”
mentioning
confidence: 80%
“…The fact that anaphylactic shock can be brought about with substances other than proteins has been established by Tomcsik (6,7), and Avery and Tillett (8) who succeeded in shocking sensitized animals by the injection of bacterial carbohydrates. The same conclusion is reached from the present experiments which demonstrate that anaphylactic shock can also be produced with synthetic substances of simple constitution.…”
Section: Methodsmentioning
confidence: 99%
“…Series/.--One group of six guinea pigs was sensitized against phage-lysed colon bacilli, grown in Uschinsky's medium (Phage 1,1K-13), another group of six animals against the intact, phage-free colon bacilli (K-13), naturally the identical bacterial strain. Six guinea pigs received sensitizing injections of phage-lysed Flexner bacilli, grown in Martin's broth (Phage 1,1-13), and an equal number was sensitized in the same manner against the intact, phage-free Flexner culture (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Four guinea pigs were sensitized with the Flexner lysate, subjected to thorough trypsinization ~ (Phage 1, 1-13 trypsinized), while four more animals were injected with uninoculated Martin's broth and Uschinsky's medium, respectively, for purpose of control.…”
Section: Methods Of Sensitization--experiments Of Zinsser and Ms Assomentioning
confidence: 99%